BESPOKE IO protocol: a multicentre, prospective observational study evaluating the utility of ctDNA in guiding immunotherapy in patients with advanced solid tumours. Issue 5 (30th May 2022) - Kasi, Pashtoon Murtaza; Chakrabarti, Sakti; Sawyer, Sarah; Krainock, Michael; Poklepovic, Andrew; Ansstas, George; Maninder, Minu; Malhotra, Meenakshi; Ensor, Joe; Gao, Ling; Eroglu, Zeynep; Ellers, Sascha; et al.
Abstract : Introduction: Immunotherapy (IO) has transformed the treatment paradigm for a wide variety of solid tumours. However, assessment of response can be challenging with conventional radiological imaging (eg, iRECIST), which do not precisely capture the unique response patterns of tumours treated with IO. Emerging data suggest that circulating tumour DNA (ctDNA) can aid in response assessment in patients with solid tumours receiving IO. The short half-life of ctDNA puts it in a unique position for early treatment response monitoring. The BESPOKE IO study is designed to investigate the clinical utility of serial ctDNA testing to assess treatment response using a tumour-informed, bespoke ctDNA assay (Signatera) and to determine its impact on clinical decision-making with respect to continuation/discontinuation, or escalation/de-escalation of immunotherapy in patients with advanced solid tumours. Methods and analysis: The BESPOKE IO is a multicentre, prospective, observational study with a goal to enroll over 1500 patients with solid tumours receiving IO in up to 100 US sites. Patients will be followed for up to 2 years with serial ctDNA analysis, timed with every other treatment cycle. The primary endpoint is to determine the percentage of patients who will have their treatment regimen changed as guided by post-treatment bespoke ctDNA results along with standard response assessment tools. The major secondary endpoints include progression-free survival, overall survival and overall response rate based on the ctDNA dynamics. Ethics and dissemination: The BESPOKE IO study was approved by the WCG Institutional Review Board (Natera-20–043-NCP BESPOKE Study of ctDNA Guided Immunotherapy (BESPOKE IO)) on 22 February 2021. Data protection and privacy regulations will be strictly observed in the capturing, forwarding, processing and storing patients' data. Natera will approve the publication of any study results in accordance with the site-specific contract. Trial registration number: NCT04761783 .